Thermal and hydrothermal treatment effects on antinutritional and functional properties of defatted winged bean (Psophocarpus tetragonolobus L.DC) seed protein powders - Saadi, Sami (2014)
The changes in the structural motif of protein by mitigating protease inhibitors like Bowman Birk Inhibitor (BBI), Kunitz type inhibitor (KTI), and lectin and other secondary metabolites such as phytic acid (PA), tannic acid (TA) and their derivative compounds of myo-inositol (MI) and gallic acid (GA) is one of the main targets of biochemists for inducing protein denaturation/unfolding and therefore, enzyme accessibility to different distinct regions of defatted protein polymeric chain (DPPC). For this reason tow method treatments named as thermal treatment (TT) and hydrothermal treatment (HT) were developed, optimized by using RSM-CCD and mathematically modeled via second order polynomial regression models to mitigate PA, MI, TA, GA, BBI, KTI and lectin after the defatting process. Under optimum conditions of TT and HT, tow model types of proteins named defatted hydrothermal treated sample (DHTS) and defatted thermal treated sample (DTTS) in addition to defatted native sample (DNS) were obtained. The subsequent digestion of the three model types (DHTS, DTTS, and DNS) with digestive enzymes of trypsin and combined trypsin-α-chymotrypsin simulated under gastrointestinal tract conditions for up six hours of hydrolysis was examined. Results showed that HT and TT conditions were successfully fitted revealing a significant correlation between dependent and independent variables, justifying the competence and accuracy of RSM-model-equations toward the formation of polymers via enzymatic hydrolysis after mitigating those polymorphic-antinutrients from defatted winged bean seeds protein (DWBSPs) matrix. The deactivation levels of KTI in the following trypsindigests (TDJ) taking DNS as control were ordered as follow: DHTS-TDJ (47.39%) > DTTS-TDJ (46.21%). In contrast, their deactivation levels for BBI in the following trypsin-α-chymotrypsin digests (TDJ-α-CHDJ) were ordered as follow: DHTS-(TDJ-α- CHDJ) 57.87% > DTTS-(TDJ-α-CHDJ) 30.23%. Moreover, many of the encountered issues can be occurred when a solid/soft materials are subjected to certain physical, and chemical stresses such as the disorder state of atoms, re-configuration of molecules, chemical bonding dissociation and re-association. Therefore, the above mechanization effects were investigated and mechanistically interpreted by determining the denaturation/unfolding state resulting from TT and HT using differential scanning calorimetry (DSC). RSM-CCD was used to determine the denaturation/unfolding efficiency (DE/UE) by exploring their energetic model parameters of enthalpy (ΔH), entropy (ΔS) and heat capacity (ΔCp). Results showed that the DE/UE (%) based ΔH, ΔS and ΔCp were found to be more precise among sample group revealing an excellent fitting between variables and highly significant R2 ranging from 99.8% (ΔCp), 91.9% (ΔS), and 84.3% (ΔH). Furthermore, the comparisons in between experimental and predicted values indicated that the corresponding RSM-CCD polynomial regression models are suitable and applicable. Meanwhile, the low level of ∆G reflected a low average level of dissociated chemical bonds and vice-versa for the high level of free energy of transition. The results of DE/UE efficiency (%) were then used with other structural parameters to investigate the enzymatic catalytic rate (ECR), enzymatic catalytic efficiency (ECEF), and other associated energetic parameters such as enzymatic activation energy (EAE) and enzymatic catalytic energy (ECE) of different enzymes with distinct region of specificities in DPPC. DNS, DHTS, and DTTS protein model types were used to assess the biochemical transition states of this catalytic elements and their involvement in many of the internal mechanisms associated to substrate aggregation, adhesion, mode of inhibitions, reversible transition, and reformation of the chemical bonding during polymer formations. Different mathematical models were successfully established in order to discriminate the mobility and displacement of specific enzymes (trypsin, α-chymotrypsin, and their interaction) with other non-specific enzyme conterparts (alcalase and papain). The results showed that the specificity of the enzymes played a key role in accelerating and retarding the ECR. They revealed that the EAE and ECE of these complex system had different signatures and profiles during their biochemical transitions, thus exhibiting competitive, noncompetitive, competitive-non-competitive and feed-back inhibition modes. They showed that these enzymes are capable in accessing different distinct of peptides or proteins, so, inducing significant dilatation (relaxation) and attraction through a chemical bombing at atomic levels. These behaviors helped us to understand the impact of enzymatic antagonism under electrostatic, ionic, cationic, hydrophobic, and hydrogen forces in renewing enzyme energy from the surrounded envirmental conditions of the hydrolysis process with profitable of released captivated biomaterials. The biological activities of the resulting biomaterials were validated by the degradation of the network structure constructed by the secondary metabolites of PA, TA and their derivative compounds MI) and GA using clustering statistical method. Results showed that, the chemical structure of the secondary metabolites played a pivotal role in maintaining their resistance against the exerted external forces, therefore, the combined effect of temperature (40°C), time (1.5hr) and pH (2.5) was the best options for degrading those antinutrients by avoiding their polymorphism (association) with DPPC that will undergo the enzymatic hydrolysis using specific enzymes (trypsin, α-chymotrypsin, and combined trypsin-α-chymotrypsin) and non-specific enzymes (papain and alcalase). The obtained enzymatic polymer digests were investigated from their antioxidative and antihypertensive biological effects in vitro using DPPH free radical scavenging assay, ferric chelating ability assay, and ABTS capacity assay, while the angiotensinconverting enzyme (ACE) inhibitory activity (IA) was assessed by HPLC, taking hippuric acid as bio-chemical marker for the identification. The majority of the enzymatic polymer digests yielded a variable range of antioxidant potency varying from low, middle, strong and very strong effects. While the ACE-IA assay revealed that these enzymatic polymer digests had the highest impact on the bioconversion of angiotensin I to angiotensin II, resulting in an overall inhibition values ranging from 89.76% to 97.99% for the four selected model types. Consequently, the DHTS of winged bean seed protein powders and their resulting enzymatic polymer digests are promising biomaterials in triggering certain biological effects similar to that of peptide likehormone such as the reduction of the incidences of the oxidation stress and hypertension.